Level of the learning skills on the young prisoners - Alizamar, Alizamar; Suri, Gusni Dian; Mudjiran, Mudjiran; Syahniar, Syahniar; Afdal, Afdal (COUNS-EDU: The International Journal of Counseling and Education, 2018)
The future achievement of adolescent in correctional institutions is also required to assume education or learning. The government has need to provide coaching for young prisoners in education at correctional institution so they are ready to enter new life after free. But the coaching that has not been able to optimally implementation. One of the problems that young prisoners is low learning skills. The purpose of this study was to describe learning skills of the young prisoners in correctional institution adolescent Tanjung Pati Lima Puluh Koto. This research used quantitative approaches with descriptive-quantitative method. The sample in this research consisted of 32 young prisoner. An analyze of the data used instruments learning skills of the young prisoners and analysis used is presentation. The research finding showed that learning skills of young prisoners at a medium level as many as 17 people with 73,91%, the very high level as many as 5 people with 21,74%, the low level as many as 1 people with 4,35%. The implication of this research is to describe learning skills young prisoners. In order, the results of this study could be data to assist the prisoners and coaching for solving their problems in learning